2012
DOI: 10.2340/00015555-1171
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effects of Plasma-mediated Bipolar Radiofrequency Ablation on Bacteria and Fungi Relevant for Wound Infection

Abstract: Infection constitutes an important part of wound pathology and impedes wound healing. Plasma-mediated bipolar radiofrequency ablation (Coblation(®)) is a tissue-removal technique suggested for use in wound treatment. The aims of this study were to determine the antimicrobial effect of ablation exposure on bacteria and fungi relevant to wound infection, and how exposure time, temperature and aerobic/anaerobic growth influence the effect. Suspensions of 10(6) colony-forming units/ml of Staphylococcus aureus, Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Some have proposed that the increasingly popular hydrosurgical system has enabled a “paradigm shift” in wound management by facilitating the removal of necrotic debris with sparing of normal tissue. 27,28 The rationale for using Coblation therapy in wound debridement stems from its ability to selectivity ablate undesired tissue. In addition to selective removal of necrotic tissue, an effective debridement method should also have the capability to reduce wound associated biofilm, which has been implicated as one of the principal factors that delays healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have proposed that the increasingly popular hydrosurgical system has enabled a “paradigm shift” in wound management by facilitating the removal of necrotic debris with sparing of normal tissue. 27,28 The rationale for using Coblation therapy in wound debridement stems from its ability to selectivity ablate undesired tissue. In addition to selective removal of necrotic tissue, an effective debridement method should also have the capability to reduce wound associated biofilm, which has been implicated as one of the principal factors that delays healing.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study 27 looked at the in situ exposure of various bacteria or fungi suspended in saline and exposed to either plasma mediated bipolar radio frequency ablation or thermal control. The suspensions were treated with either Coblation or thermal energy for exposure times of 0.5, 1.0, or 2.0 seconds.…”
Section: Principles Of Plasma-mediated Bipolar Radio Frequency Ablatimentioning
confidence: 99%
“…This plasma can break molecular bonds within the tissues at relatively low temperatures (40–70°C), and thus remove the necrotic tissue with minimal damage to normal healthy tissue . PBRA has been shown to have significant microbicidal effects compared to other methods of debridement in vitro, and in vivo in porcine models . A recent study reported PBRA as easy to use, safe and effective when used in the outpatient department on six patients with chronic leg ulcers .…”
Section: Plasma‐mediated Bipolar Radiofrequency Ablationmentioning
confidence: 99%
“…These results are in agreement with the results of Bowling et al (19) which evaluated the effect of Versajet on bacterial spread in an operating room setup. A previous study showed that Coblation in vitro has a bactericidal effect of 4-5 log reduction on planktonic solutions of S. aureus, Streptococcus pyogenes, Pseudomonas aeruginosa and E. coli at 0.5-2.0 s exposure (17). The current study confirms the bactericidal effect of Coblation and a similar 4-5 log reduction of S. aureus in an ex vivo porcine wound biofilm model, and a likely reason for this effect is that Coblation has a direct bactericidal effect, rather than merely removing the bacteria from the wound bed as would be the aim of Versajet and curette debridement.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore very different from the effect produced by conventional electrosurgical devices that use radiofrequency to generate heat and disintegrate tissue at high temperatures without plasma formation (15,16). A previous study has shown that this technique has a microbicidal effect on microbes involved in wound infection, which seems to be a direct effect of the plasma field (17). The Coblation probe used for wound debridement flushes saline over the electrodes and has a suction line for evacuation of saline and debrided tissue material.…”
mentioning
confidence: 98%